Vitali, Gernsheim, Newhall, Soby, 1956-1961. Intorno ad alcune mostre di fotografia a Milano - Paoli, Silvia (Rivista di studi di fotografia. Journal of Studies in Photography, 2015)
During the 1950s, Lamberto Vitali, a prominent collector, art historian, and photography connoisseur, promoted and curated several exhibitions in Milan, including Cartier-Bresson, the Gernsheim Collection, 19th-century Italian photography, Werner Bischof, Robert Capa, and The Family of Man. Based on original documents and private correspondence with such interlocutors as Helmut Gernsheim, Beaumont Newhall, James Thrall Soby, and Alfred H. Barr Jr., this essay discusses Vitali’s crucial role in earning Milan a prominent place in the international circuit of post-war photographic culture.